2021
DOI: 10.1109/jiot.2021.3075561
|View full text |Cite
|
Sign up to set email alerts
|

Collection of Data With Drones in Precision Agriculture: Analytical Model and LoRa Case Study

Abstract: Unmanned Aerial Vehicles (UAVs) are autonomous devices employed as data collectors in precision agriculture to support a large number of applications. These UAVs gather data from on-the-ground wireless sensor networks, especially in scenarios that lack any kind of fixed communication infrastructure or where the available infrastructure does not fit the application requirements. Sensors on the ground can store sensing data, and in scenarios that do not require a real-time observation and analysis of the data, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(10 citation statements)
references
References 40 publications
0
9
0
1
Order By: Relevance
“…The proposed protocol extends LoRa transmission range compared with the one-hop links, as well as being robust against network dynamic topology changes. Considering a UAV as an aerial gateway, the authors of [9] optimized UAV's altitude to efficiently collect data from ground IoT devices, in a precision agriculture use case. Finally, the authors in [10] supported a disaster management application where LoRa is used for the UAV-IoT device link, while Wi-Fi handles the UAV-gateway communication.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed protocol extends LoRa transmission range compared with the one-hop links, as well as being robust against network dynamic topology changes. Considering a UAV as an aerial gateway, the authors of [9] optimized UAV's altitude to efficiently collect data from ground IoT devices, in a precision agriculture use case. Finally, the authors in [10] supported a disaster management application where LoRa is used for the UAV-IoT device link, while Wi-Fi handles the UAV-gateway communication.…”
Section: Introductionmentioning
confidence: 99%
“…The clustering algorithm and Travelling Salesman Problem (TSP) based routing was presented in [ 35 ] to establish the path between sensor nodes and BS through UAV. In [ 36 ], LoRa communication technology was utilized to establish the communication between the UAV and on-ground sensors and collect the data from the agriculture field periodically. Policy-iteration based path planning algorithm was applied in routing formation which avoids the inter-unmanned surface vehicle collision [ 37 ].…”
Section: Related Workmentioning
confidence: 99%
“…In the proposed methodology mode of communication, distance between transmitter receiver, drone trajectory path and the velocity of the drone plays a key role in successful data collection. The authors developed a model with the forementioned parameters; also observed other parameters like field shape drone flight plan and sensors utilized could also affect the data gathered (14). Jaeuk Baek et al studied on UAV as flying data collector and wirelessly energize the devices or IoT sensors on ground utilizing wireless charging sensor networks.…”
Section: Literature Surveymentioning
confidence: 99%